6/179
\begin{frame}
  \frametitle{Rules for $\wedge$ and $\vee$}
  
  \begin{goal}{Introduction of $\wedge$}
    \vspace{-1ex}
    \begin{align*}
      \infer[\rulename{\wedge_i}]
      {\phi \wedge \psi}
      {\phi && \psi}
    \end{align*}
    (If you have derived $\phi$ and $\psi$, then you can conclude $\phi \wedge \psi$.)
  \end{goal}
  \pause
    
  \begin{goal}{Elimination of $\wedge$}
    \vspace{-1ex}
    \begin{align*}
      \infer[\rulename{\wedge_{e_1}}]
      {\phi}
      {\phi \wedge \psi}
      &&
      \infer[\rulename{\wedge_{e_2}}]
      {\psi}
      {\phi \wedge \psi}
    \end{align*}
  \end{goal}
  \pause\medskip

  \begin{goal}{Rules for $\vee$}
    \vspace{-1ex}
    \begin{align*}
      \infer[\rulename{\vee_{i_1}}]
      {\phi \vee \psi}
      {\phi}
      &&
      \infer[\rulename{\vee_{i_2}}]
      {\phi \vee \psi}
      {\psi}
    \end{align*}
  \end{goal}
\end{frame}